2017
DOI: 10.3390/cli5030046
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming and Tea Production—The Bibliometric View on a Newly Emerging Research Topic

Abstract: Abstract:In this study, we analyzed the newly emerging research field of climate change in combination with tea production. We adapted a valid search query to cover the relevant literature as completely as possible and to exclude irrelevant literature. The search resulted in a publication set of 14 key papers dealing with the implications of climate change for tea production as well as 71 papers citing at least one of the 14 key papers. The VOSviewer software was used for revealing the thematic content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…We conducted a bibliometric review to identify the underlying network linkages in published literature using the VOSviewer software. Bibliometric techniques have been used to explore research trends in fields such as molecular research [23], transplant medicine [24], climate science [25] and even medical tourism [18]. Policy researchers have likewise used these methods to examine the literature on policy implementation [26] and policy learning [27], research in health policy [28] and the policy sciences [29,30], and the evolution of science and technology policies [31].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a bibliometric review to identify the underlying network linkages in published literature using the VOSviewer software. Bibliometric techniques have been used to explore research trends in fields such as molecular research [23], transplant medicine [24], climate science [25] and even medical tourism [18]. Policy researchers have likewise used these methods to examine the literature on policy implementation [26] and policy learning [27], research in health policy [28] and the policy sciences [29,30], and the evolution of science and technology policies [31].…”
Section: Discussionmentioning
confidence: 99%
“…Marx et al (2017) identified 14 articles highlighting that shifts in rainfall and solar radiation influence tea yields and quality with implications for farmer livelihoods. For example, Biggs et al (2018) demonstrate that climate change is impacting farmer livelihoods across four major tea-growing regions of Assam, India.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the significance of accurately modelling tea species' responses to a changing climate, numerous studies have been devoted to individual country assessments. Alarming evidence of climate change in the tea-growing areas of Sri Lanka, Kenya, India and China are attributed to the rising temperature, variability in rainfall, and increasing incidences of extreme events [9,22]. Using climate model projections, Jayasinghe and Kumar [23] found that regions of Sri Lanka that have been best suited for growing tea will undergo a suitability decline of about 10.5% over the course of the next 30 to 50 years.…”
Section: Introductionmentioning
confidence: 99%